A Review on Potential Mechanisms of Terminalia chebula in Alzheimer's Disease. (28th January 2016) - Afshari, Amir R.; Sadeghnia, Hamid R.; Mollazadeh, Hamid
Abstract : The current management of Alzheimer's disease (AD) focuses on acetylcholinesterase inhibitors (AChEIs) and NMDA receptor antagonists, although outcomes are not completely favorable. Hence, novel agents found in herbal plants are gaining attention as possible therapeutic alternatives. The Terminalia chebula (Family: Combretaceae) is a medicinal plant with a wide spectrum of medicinal properties and is reported to contain various biochemicals such as hydrolysable tannins, phenolic compounds, and flavonoids, so it may prove to be a good therapeutic alternative. In this research, we reviewed published scientific literature found in various databases: PubMed, Science Direct, Scopus, Web of Science, Scirus, and Google Scholar, with the keywords: T. chebula, AD, neuroprotection, medicinal plant, antioxidant, ellagitannin, gallotannin, gallic acid, chebulagic acid, and chebulinic acid. This review shows that T. chebula extracts and its constituents have AChEI and antioxidant and anti-inflammatory effects, all of which are currently relevant to the treatment of Alzheimer's disease.